The warrior's innocent captive - Matthews, Ella (Harlequin historicals., 2021)
"An impossible choice: His family or love. Born into different worlds, formidable steward Erik Ward could only admire sheltered noblewoman Linota Leofric from afar. Now he must escort Linota on a dangerous journey--a route that could also enable Erik to finally find his missing sister. Only when Linota is kidnapped, Erik must stop at nothing to save her, and ultimately faces an impossible choice: his vulnerable sister--or the courageous beauty in his arms..."--Provided by pubisher.